The Contribution of Membrane Vesicles to Bacterial Pathogenicity in Cystic Fibrosis Infections and Healthcare Associated Pneumonia - Vitse, Jolien; Devreese, Bart (Frontiers in Microbiology, 2020)
Almost all bacteria secrete spherical membranous nanoparticles, also referred to as membrane vesicles (MVs). A variety of MV types exist, ranging from 20 – 400 nm in diameter, each with their own formation routes. The most well-known vesicles are the outer membrane vesicles (OMVs) which are formed by budding from the outer membrane in Gram-negative bacteria. Recently, other types of MVs have been discovered and described, including outer-inner membrane vesicles (OIMVs) and cytoplasmic membrane vesicles (CMVs). The former are mainly formed by a process termed endolysin-triggered cell lysis in Gram-negative bacteria, the latter are formed by Gram-positive bacteria. MVs carry a wide range of cargo, such as nucleic acids, virulence factors and antibiotic resistance components. Moreover, they are involved in a multitude of biological processes that increase bacterial pathogenicity. In this review, we discuss the functional aspects of MVs secreted by bacteria associated with nosocomial pneumonia and cystic fibrosis. We mainly focus on how MVs are involved in virulence, antibiotic resistance, biofilm development and inflammation that consequently aid these bacterial infections.